(untitled) (Third Sector Social Economic Review, 2025)
This study aims to examine the impact of inclusive leadership on innovative work behavior, which is strategically significant for organizational success in today’s increasingly competitive business environment, and to explore the potential mediating role of psychological safety in this relationship. Employing a quantitative research design with a cross-sectional approach, the sample consists of 491 employees working in private sector organizations located in the provinces of Kastamonu and Çankırı. Data were collected using a convenience sampling method and analyzed via R software version 4.2.2. The findings reveal a statistically significant, strong, and positive relationship between inclusive leadership and innovative work behavior. However, one of the study’s notable and original findings indicates that the mediating effect of psychological safety in the relationship between inclusive leadership and innovative work behavior was not statistically significant. These results underscore the importance of prioritizing inclusive leadership competencies in leadership development programs and suggest that the underlying psychological mechanisms of such relationships may vary across cultural contexts. Accordingly, the study contributes to the literature on leadership and innovation and offers context-sensitive strategic insights for practitioners.